An Observational Study of Pseudodefect of Tibial Plafond (Incidence, Characteristics and Different Parametric Correlations) - Zakariya Ahmed, Shayma; Abdulrahman Rashid , Sameeah (Diyala Journal of Medicine, 2022)
Background: The notch of Harty is a normal variant radiologically and incidentally diagnosed finding but can be mistaken as pathology. Objective: To identify the incidence and characteristic findings of the notch of Harty. Patients and Methods: A cross-sectional study was conducted on 121 patients referred to the Radiology department, MRI unit, to undergo ankle MRI through a one-year period (January to December 2020). Cases with significant ankle lesions were excluded. All MRI studies were performed on 1.5 T MR scanners (Aera, Siemens, Arlington). Results: The notch of Harty was present in 35.5% patients; their age ranged from 5-83 years with a mean age of 38.20 years. The average width of the notch was 5.65mm while the mean depth was 1.04 mm. There was no significant correlation between the presence of the notch of Harty and findings such as rheumatic arthritis, minor trauma, chondral thinning. However, there was significant correlation between the presence of the notch of Harty and subjacent subchondral sclerosis. Conclusion: The notch of Harty was present among a considerable number of cases with no sex predominance. The notch might be misinterpreted by radiologists as true osteochondral lesions, thus, familiarity with location and appearance of these pseudodefects will avoid their misinterpretation. Keywords: The notch of Harty, pseudodefects, MRI, tibial plafond, osteochondral lesions